Analysis of Physiological Factors (High Fundus Uteri and Premature Rupture of Membranes) and Psychological (Cemas) on Labor Pain in Hospital Women in Working Areas of Health Center Sambirejo Banyuwangi District 2018 - Suciningtyas, Endang; Indasah; Sari, Nia (Journal for Research in Public Health, 2020)
Labor is the expenditure of the results of conception that have been able to live outside the womb through several processes such as the thinning and opening of the cervix, and the presence of contractions that take place at certain times without complications. Pain in labor is a manifestation of the contraction (shortening) of the uterine muscle. This contraction causes pain in the waist, abdomen and radiates towards the thigh. The cause of labor pain includes physiological factors such as the height of the fundus uterus and premature rupture of the second factor, namely psychological, such as anxiety. The purpose of the study was to determine the factors that affect labor pain in mothers in the work area of ​​Sambirejo Public Health Center, Banyuwangi Regency. The research design used was cross sectional. The study population was all mothers giving birth in the work area of ​​Sambirejo Community Health Center and a large sample of 50 patients using random sampling. Data collection uses observation sheets, checklists and questionnaires then analyzed using multiple linear regression tests. The results showed that there was no effect of uterine fundal height (TFU) on labor pain in Sambirejo Public Health Center, Banyuwangi Regency (significant value = 0.835> 0.05). There was the effect of early rupture of membranes (KPD) on labor pain in Sambirejo Health Center in Banyuwangi Regency (significant value = 0.029 <0.05) and there was anxious influence on labor pain in Sambirejo Health Center Banyuwangi District (significant value = 0.040 <0.05). Based on the results of statistical decisions, if the significance is <a (0.001 <0.05) then Ho is rejected, meaning TFU (X1), KPD (X2), and anxiety (X3) simultaneously has a significant effect on labor pain (Y) at Sambirejo District Health Center Banyuwangi. Based on this research, it can be used as an effort to educate or promote health and counseling pregnant women about the importance of preventive efforts to reduce pain during childbirth